Cretan Institutional Inscriptions: A New EpiDoc Database - Irene Vagionakis (Journal of the Text Encoding Initiative)
The paper presents the database Cretan Institutional Inscriptions, which was created as part of a PhD research project carried out at the University of Venice Ca’ Foscari. The database, built using the EpiDoc Front-End Services (EFES) platform, collects the EpiDoc editions of six hundred inscriptions that shed light on the institutions of the political entities of Crete from the seventh to the first century BCE. The aim of the paper is to outline the main issues addressed during the creation of the database and the encoding of the inscriptions and to illustrate the core features of the database, with an emphasis on the advantages deriving from the combined use of the TEI-EpiDoc standard and of the EFES platform.